A Practical KM 3.0 System Model With Semantic Web 3.0 Technology - Chen, Te Fu (Journal of Knowledge Management Practice, 2011)
Looking at factors like value, scope and expiration date, it shouldn’t come as a surprise that the "collect everything" mentality of KM 1.0 was a failure. Adding factors like maintenance cost and information overload, it shouldn’t be very surprising that the "share everything" mentality of KM 2.0 is risking failure as well. We cannot treat knowledge as one thing, but rather as a diverse range of subjects which can be useful to someone in some situations. The philosophy of KM 3.0 is focused on the individual, and the use of knowledge. The study will integrate web 3.0 technology into KM 3.0 system to collect, share and use valuable knowledge to help people get their job done. Therefore, the study will construct a practical KM 3.0 system model with semantic Web 3.0 technology. Semantic Web 3.0 is about making all this technology and content (on the Web) smarter – by adding semantics to the data and by adding more smarts to applications so that they can do a better job of helping humans. Semantic Web 3.0 technology will undoubtedly change how we interact and access information/knowledge both within and outside the firewall and people. The semantic Web provides an approach that fosters richer repositories with better and smarter tags. It promises to be a system where people, knowledge and information co-exist, content is easily searched and accessed, and information/knowledge is relevant and of high quality. The nature of your organization should determine the type of knowledge management system(s) you should implement. Focus should no longer be on simply collecting or sharing everything and anything, but rather on use to avoid information overload. Every organization is different, so the study will not provide a blueprint for everyone to use, but rather give an example of how you could analyze and determine which knowledge management system(s) that will fit your organization.